2019
DOI: 10.1245/s10434-019-07344-5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Evaluating Bioimpedance Spectroscopy Versus Tape Measurement for the Prevention of Lymphedema Following Treatment for Breast Cancer: Interim Analysis

Abstract: BackgroundBreast cancer-related lymphedema (BCRL) represents a major source of morbidity among breast cancer survivors. Increasing data support early detection of subclinical BCRL followed by early intervention. A randomized controlled trial is being conducted comparing lymphedema progression rates using volume measurements calculated from the circumference using a tape measure (TM) or bioimpedance spectroscopy (BIS).MethodsPatients were enrolled and randomized to either TM or BIS surveillance. Patients requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…While studies have shown a lower incidence in lymphedema severity amongst breast cancer patients after treatment when undergoing early surveillance with BIS compared to a traditional referral model of care [ 30 ], there are no reports directly comparing the efficacy of early surveillance models leveraging BIS versus using limb volume changes. BIS has only been found to have modest correlation to Perometer, with one study finding R = 0.60 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown a lower incidence in lymphedema severity amongst breast cancer patients after treatment when undergoing early surveillance with BIS compared to a traditional referral model of care [ 30 ], there are no reports directly comparing the efficacy of early surveillance models leveraging BIS versus using limb volume changes. BIS has only been found to have modest correlation to Perometer, with one study finding R = 0.60 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The included studies also highlight the need for reliable measurements and definitions of subclinical lymphedema. Both percentage increase compared to pre-surgery measurements [16,18,19] as well as increase in volume difference between the limbs were applied [5]. However, by long-term follow-up volume difference between the limbs always has to be taken into account, due to body weight change and thereby normal change of limb volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings from a randomized, controlled trial (n ¼ 508) evaluating the effect of prospective lymphedema surveillance on lymphedema incidence, comparing the use of bioimpedance spectroscopy (BIS) versus tape measure (TM) to investigate early lymphedema treatment (compression sleeve) also provide some insight into the potential role of compression as tertiary prevention [19]. This trial implemented compression sleeves for a minimum of 4 weeks for those women whose BIS or TM measurements exceeded their preclinical lymphedema threshold.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…Alternatively, this ratio may be linearised and expressed as an L-Dex score with the normal range being between − 10 and + 10 [ 22 ]. A change of + 6.5 L-Dex units from baseline is considered a trigger of sub-clinical lymphoedema [ 19 , 29 ]. This device is portable and can be operated easily by an individual completing self-measurements within a home environment with access to power and a wireless internet network.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective surveillance and early intervention model of care has been recognised as an optimal framework for the early detection and management of sub-clinical lymphoedema [ 13 15 ]. Using prospective surveillance model in clinical practice enables the early identification and intervention for lymphoedema, sometimes in a sub-clinical stage, where intervention can prevent progression to a chronic condition [ 16 19 ]. Recommended practice for the prospective surveillance model requires that individuals at risk of lymphoedema regularly attend clinics on a 3–6 monthly cycle according to their risk factors and treatment pathway for three years to have their arm monitored for lymphoedema by either using bioimpedance spectroscopy (BIS) or circumference measurements [ 13 , 16 ]…”
Section: Appendixmentioning
confidence: 99%